IDENTIFIKASI KEKUATAN DAN KELEMAHAN KOMPONEN SISTEM INFORMASI IKLIM(STRENGTH AND WEAKNESS IDENTIFICATION OF CLIMATE INFORMATION COMPONENT) - Urip Haryoko (Agromet, 2008)
Based on the survey of climate information application in many sectors showed that climate informations are inaccurate, lately received, abstrused and not meet to the user activities. There is a big gaps between climate information producer and user, it needs a bridging to handle a problem in interpreting information. These conditions caused to not optimally climate risk anticipation, so that there were still a lot of failures in some sectors, i.e. crops failure, urban floods, food and water shortage, health crisis, forest fire, etc. There are many activities have been done to increase skill to intepret and react to climate information. Providing climate information is one of the methods to minimize the climate risk. By understanding the climate information, climate risk could be managed optimally and it can minimize negative impact of climate extreme and get benefit from good climate conditions. Boer, 2009, said that there are five primary components as a key to climate information application in manage a risk, 1) climate data observation and data analysis, 2) climate forecast/prediction system, 3) climate information production and evaluation system, 4) communication and dissemination system, and 5) climate information system. Valuation of strength and weakness of five components above relatively depends on which angel be used. It needs an objective indicator to evaluate those components. In this paper, strength and weakness of climate information components will be identified. Data was collected from Meteorological, Climatological and Geophysical Agency’s stations and some institutions in Banten Province as climate information users by distributing questionaire. Furthermore, based on the components identification it could be created a strategy how to increase the capacity of climate information applications.